2015
DOI: 10.1016/j.jbiomech.2015.10.025
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural alterations of osteocyte morphology via loaded implants in rabbit tibiae

Abstract: Osteocytes are crucial cells that control bone responses to mechanical loading. However, the effects of mechanical loading on osteocytes around dental implants are unclear. The aim of this study was to investigate whether mechanical loading via bone-integrated implants influences osteocyte number and morphology in the surrounding bone. Fourteen anodized Ti-6Al-4V alloy dental implants were placed in seven Japanese white rabbits, and implants in each rabbit were subjected to mechanical loading (50N, 3Hz for 180… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
21
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 35 publications
4
21
0
Order By: Relevance
“…In our study using dental implants, mechanical repetitive loading improved bone architecture by upregulation of osteocyte number and dendrite processes with preferential alignment of BAp c-axis/collagen fibers [22,125]. Moreover, we also demonstrated that preferential alignment of osteocytes is in accordance with the principal direction of mechanical load in an animal model using hip implants [96].…”
Section: Osteocytes In Bone Tissuesupporting
confidence: 65%
See 1 more Smart Citation
“…In our study using dental implants, mechanical repetitive loading improved bone architecture by upregulation of osteocyte number and dendrite processes with preferential alignment of BAp c-axis/collagen fibers [22,125]. Moreover, we also demonstrated that preferential alignment of osteocytes is in accordance with the principal direction of mechanical load in an animal model using hip implants [96].…”
Section: Osteocytes In Bone Tissuesupporting
confidence: 65%
“…Recently, we have demonstrated that osteocytes become more spherical with increased dendrite processes under loaded conditions. Additionally, the number of osteocytes around dental implants significantly increased under loaded conditions, strongly suggesting that mechanical stimuli via dental implants change osteocyte shape and development of osteocyte network [125]. Hence, morphological alterations of osteocytes in response to mechanical stimuli may play an important role in controlling bone quality.…”
Section: Mechanosensation In Osteocytesmentioning
confidence: 99%
“…Nevertheless, the characterization of the LCN remains difficult today due its location embedded within the opaque, mineralized matrix and its complexity. Conventional 2D imaging techniques such as light microscopy 10,11 , transmission electron microscopy (TEM) 12 , scanning electron microscopy (SEM) 13 , and atomic force microscopy (AFM) 14 have been previously used to investigate the LCN. Based on 2D data, lacunae are typically described as flattened ellipsoids with an average area of about 20-70 µm 2 , an average length of about 14-25 µm and an average width of about 5-10 µm 15,16 , and the canaliculi are described as channels with an average diameter of about 100-600 nm 17,18 .…”
mentioning
confidence: 99%
“…The scanner software (Inveon Acquisition Workplace 2.2, Siemens Inc., Germany) was applied for image reconstruction and analyses. The bone around the implant with 0.5 mm thickness and 5.5 mm length (including 5 mm length of implant and 0.5 mm length of bone under the implant) was chosen as the region of interest (ROI) in each sample for microstructure analyses 26 (Fig. 2a), and parameters such as trabecular bone volume/total volume (Tb.BV/TV, %), trabecular number (Tb.N, mm −1 ), trabecular thickness (Tb.Th, mm), trabecular separation (Tb.Sp, mm) and bone mineral density (BMD, mg/cc) were measured.
Figure 2Results of Micro-CT scan and analyses.
…”
Section: Methodsmentioning
confidence: 99%